Iridoids and polyphenols from chilean Gaultheria spp. berries decrease the glucose uptake in Caco-2 cells after simulated gastrointestinal digestion. (1st February 2022) - Mieres-Castro, Daniel; Theoduloz, Cristina; Sus, Nadine; Burgos-Edwards, Alberto; Schmeda-Hirschmann, Guillermo; Frank, Jan; Jiménez-Aspee, Felipe
Highlights: The effect of in vitro gastrointestinal digestion on Gaultheria fruits was studied. Low stability of anthocyanins, iridoids and hydroxycinnamic acids was observed. Food matrix increased stability of compounds but decreased their bioaccesibility. Bioaccessible extracts and compounds decreased glucose uptake in Caco-2 cells. Decrease in SGLT1, GLUT2, GLUT5 and SI mRNA expression in Caco-2 cells was observed. Abstract: Berries are rich food sources of potentially health-beneficial (poly)phenols. However, they may undergo chemical modifications during gastrointestinal digestion. The effect of simulated gastrointestinal digestion on the content and composition of secondary metabolites from Gaultheria phillyreifolia and G. poeppigii berries was studied. The influence of the digested extracts on the in vitro metabolism and absorption of carbohydrates was evaluated. After simulated digestion, 31 compounds were detected by UHPLC-DAD-MS. The total content of anthocyanins decreased by 98–100%, flavonols by 44–56%, phenylpropanoids by 49–75% and iridoids by 33–45%, the latter showing the highest stability during digestion. Digested extracts inhibited α-glucosidase (IC50 2.8–24.9 μg/mL) and decreased the glucose uptake in Caco-2 cells by 17–28%. Moreover, a decrease in the mRNA expression of glucose transporters SGLT1 (38–92%), GLUT2 (45–96%), GLUT5 (28–89%) and the enzyme sucrase-isomaltase (82–97%) was observed. These results show the effect of simulated gastrointestinal digestion on the content and composition of Gaultheria berries.